STUDI KOMPARATIF TINGKAT KESEJAHTERAAN MASYARAKAT BERDASARKAN AKSESIBILITAS DAERAH DI KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA - Putriana, Ria; Rianto, Slamet; Farida, Farida (Pendidikan Geografi, 2013)
This study aims to determine the comparative level of social welfare based on the accessibility of the area in the district of Pulau Punjung Dharmasraya. This research is a comparative descriptive studies. The population in this study house holds (KK) in District Dharmasraya Pulau Punjung, the population Nagari Sungai Dareh, Sungai Kambut, IV Koto Pulau Punjung, Sikabau and Tebing Tinggi. Samples were taken in two ways, the samples were taken by purposive sampling areas (designation) with proportional random sampling with a proportion of 3% of the sample so research sample was 170 households. The research found that: (1) there are differences in the level of welfare of the people seen on the fulfillment of basic needs among Sungai Kambut and Nagari Sungai Dareh with value t = -3.707 127.868 degrees of freedom, while ttable (n = 170) at the 5% significance level is - 1,662. Thus the value of t is less than t table, means the level of social welfare Nagari Sungai Dareh better than Sungai Kambut, (2) There are differences in the level of prosperity seen from the clothing needs of the community and Nagari Sungai Kambut between Sungai Dareh with t value = - 2,947 degrees of freedom 167.97, while the t table (n = 170) at the 5% significance level is -1.662. Thus the value of t is less than t table, means the level of social welfare Sungai Nagari riDareh better than da Sungai Kambut, (3) There are differences in the level of welfare of the people seen on the board needs Sungai Kambut and Nagari Nagari Sungai Dareh with value t = - 3,194 degrees of freedom 161.824, while the t table (n = 170) at the 5% significance level is -1.662. Thus the value of t is smaller than TTable, means the level of social welfare Nagari Sungai Dareh better than Sungai Kambut